Media Narratives on Eating Disorders in the Spanish Press (2012-2022): Representation, Discourse, and Stigmatization - Maria Comabella-Costa; Marta Consuegra-Fernández; Joan-Gabriel Burguera-Serra (Revista Mediterránea de Comunicación)
Purpose. To analyze how the Spanish press represents eating disorders (EDs) through personal narratives and to assess the impact of these media portrayals on social perceptions of these conditions. Methodology. A content analysis was conducted on 136 articles published in four Spanish newspapers (El País, ABC, La Vanguardia, and El Mundo) between 2012 and 2022, identifying representation patterns and protagonist characteristics. Results and conclusions. Findings confirm that ED stories in the media predominantly feature women (93.38%), particularly young individuals aged 20 to 35 (52.94%). Anorexia nervosa is the most frequently portrayed disorder (63.24%), whereas bulimia nervosa (17.65%) and binge-eating disorder (15.44%) receive significantly less coverage. The analyzed testimonies mostly focus on well-known public figures (74.26%), linking EDs with the entertainment industry and reinforcing sociocultural stereotypes that may contribute to stigmatization. Novelty. This study provides a critical perspective on the role of the media in shaping narratives about EDs and highlights the need for communication strategies that avoid reductionist approaches and promote a more comprehensive and empathetic understanding of these disorders.